Methicillin-Resistant Staphylococcus aureus: Risk Factor, Prevalence and Antimicrobial Susceptibility Pattern among Pregnant Women at Mater Miscericordia Hospital, Nigeria - Chinyere, Chimaobi, Charity; Chimaobi, Okoronkwo; Mmaduabuchi, Egwu-Ikechukwu, Modesta; Magareth, Ali Chioma; Aina, Adeshina Afusat; Sunday, Ugwuocha Chibuike; Geraldine, Ikwuakor Chinyere (Journal of Advances in Microbiology, 2025)
Staphylococcus aureus especially some types of methicillin-resistant Staphylococcus aureus” (MRSA) is the major cause of both community and hospital acquired infection globally. us infections. The aim of this study was to determine the risk factors, prevalence and antimicrobial susceptibility pattern of methicillin-resistant Staphylococcus aureus (MRSA) isolated from urine samples of pregnant women attending ante-natal clinics in Mater Miscericordia hospital Afikpo, Ebonyi State. A total of one hundred and fifty (150) urine samples were collected from pregnant women, attending ante-natal clinics in Mater hospital Afikpo, Ebonyi State, and transported to Microbiology laboratory of Ebonyi State university within two hours of collection. The samples were inoculated unto nutrient broth for overnight incubation for enrichment. They were then sub-cultured aerobically at 370C onto Mannitol salt agar (MSA) plates for 24hrs. Then the plates were examined to quantify the organisms present according to Clinical Laboratory Standard Institute (CLSI) guidelines. Antimicrobial susceptibility was carried out using disc diffusion method. Out of the 150 urine samples analyzed, 61(40.7%) were positive for Staphylococcus aureus. The 61 Staphylococcus aureus was further screened for MRSA, 20 was shown to be MRSA positive (36.0%).  S. aureus and MRSA were shown to be more prevalent among pregnant women of age 23-27years of age and 38-42 years 46% and 100% respectively. Pregnant women who are civil servants has the highest MRSA (40%), MRSA was also high among the pregnant women who are had tertiary level of education (23%), Finally, those in their second trimester had 45% MRSA.  Antimicrobial susceptibility results showed that S. aureus was highly resistance to all the 10 antibiotics subjected to; oxacillin (97%), ceftriaxone (100%), gentamycin (97%), clindamycin (100%), tetracycline (92%), cefotaxin (100%), erythromycin (100%S) vancomycin (100%) and ciprofloxacin (95%), except for imipenem (61%) that are susceptible. The burdens of MRSA can be dealt with and reduced if the result from this research is considered as a guide during ante-natal care awareness/sensitization in the hospitals.